2022
DOI: 10.3390/antibiotics11091239
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Area under the Concentration-Time Curve Estimation Using Bayesian Modeling versus First-Order Pharmacokinetic Equations: A Quasi-Experimental Study

Abstract: Aim: To evaluate the efficiency of Bayesian modeling software and first-order pharmacokinetic (PK) equations to calculate vancomycin area under the concentration-time curve (AUC) estimations. Methods: Unblinded, crossover, quasi-experimental study at a tertiary care hospital for patients receiving intravenous vancomycin. Vancomycin AUC monitoring was compared using Bayesian modeling software or first-order PK equations. The primary endpoint was the time taken to estimate the AUC and determine regimen adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Software integration would reduce staff workload, for example, avoiding manual data collection and report publication, thus reducing costs. This has been demonstrated in a recent study where integration of a Bayesian modelling software into the electronic health record reduced the time for reporting from a median of 9.3 to 3.8 min 15 . Transitioning to a pharmacist‐led approach could further streamline resource needs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Software integration would reduce staff workload, for example, avoiding manual data collection and report publication, thus reducing costs. This has been demonstrated in a recent study where integration of a Bayesian modelling software into the electronic health record reduced the time for reporting from a median of 9.3 to 3.8 min 15 . Transitioning to a pharmacist‐led approach could further streamline resource needs.…”
Section: Discussionmentioning
confidence: 97%
“…This has been demonstrated in a recent study where integration of a Bayesian modelling software into the electronic health record reduced the time for reporting from a median of 9.3 to 3.8 min. 15 Transitioning to a pharmacist-led approach could further streamline resource needs. Pharmacists are commonly embedded in treating teams and could facilitate dose recommendation acceptance and improve team knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that vancomycin concentrations in the 1-level group were usable in 88.2% of patients compared with 48.3% of the 2-level monitoring group ( P = 0.001). 18 Both of these results are important because it suggests the utility that 1-level Bayesian dosing does not rely on a specifically timed draw to best predict AUC and monitoring of patients.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, one study found that Bayesian modeling allowed for 88.2% of usable vancomycin concentrations, compared with 48.3% when using first-order pharmacokinetic equations to estimate AUC. 2 In addition to alleviating logistical concerns, collecting a single vancomycin concentration may also have a cost-beneficial effect. 3 Pharmacokinetic analyses by Neely et al 4 and Shingde et al 5 have demonstrated a high level of accuracy when estimating vancomycin AUC with a single concentration in nonobese adults.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, one study found that Bayesian modeling allowed for 88.2% of usable vancomycin concentrations, compared with 48.3% when using first-order pharmacokinetic equations to estimate AUC. 2 In addition to alleviating logistical concerns, collecting a single vancomycin concentration may also have a cost-beneficial effect. 3…”
Section: Introductionmentioning
confidence: 99%